Emerging biomarkers for non-invasive diagnosis and treatment of cancer: a systematic review - Zakari, Suleiman; Niels, Nguedia K.; Olagunju, Grace V.; Nnaji, Precious C.; Ogunniyi, Oluwabusayo; Tebamifor, Mercy; Israel, Emmanuel N.; Atawodi, Sunday E.; Ogunlana, Olubanke Olujoke (Frontiers in Oncology, 2024)
Cancer remains a global health challenge, necessitating continuous advancements in diagnostic and treatment strategies. This review focuses on the utility of non-invasive biomarkers in cancer diagnosis and treatment, their role in early detection, disease monitoring, and personalized therapeutic interventions. Through a systematic review of the literature, we identified 45 relevant studies that highlight the potential of these biomarkers across various cancer types, such as breast, prostate, lung, and colorectal cancers. The non-invasive biomarkers discussed include liquid biopsies, epigenetic markers, non-coding RNAs, exosomal cargo, and metabolites. Notably, liquid biopsies, particularly those based on circulating tumor tumour DNA (ctDNA), have emerged as the most promising method for early, non-invasive cancer detection due to their ability to provide comprehensive genetic and epigenetic information from easily accessible blood samples. This review demonstrates how noninvasive biomarkers can facilitate early cancer detection, accurate subtyping, and tailored treatment strategies, thereby improving patient outcomes. It underscores the transformative potential of noninvasive biomarkers in oncology, highlighting their application for enhancing early detection, survival rates, and treatment precision in cancer care.